2012
DOI: 10.1111/j.1365-2109.2012.03207.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of feed-based adjuvant vaccine againstStreptococcus agalactiaeinOreochromisspp. in Malaysia

Abstract: This study was conducted to determine the systemic, mucosal immunity and protective capacity of the feed‐based adjuvant vaccine (FAV) of Streptococcus agalactiae following oral vaccination against streptococcosis in tilapias. Two hundred and sixteen red tilapia fish were divided into three major groups. Each major group consisted eight tilapia kept in nine 2000 L glass aquaria. At day 0, all fish from the FAV group were fed with feed that had been incorporated with an adjuvant, while fish in the feed‐based va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 32 publications
4
47
0
Order By: Relevance
“…Nur-Nazifah et al [13] compared the efficacy of a recombinant vaccine encoding the LPXT cell wall surface anchor family protein of S. agalactiae with an IWC-vaccine in which they showed that both vaccines produced high IgM levels in serum and mucus that corresponded with low post challenge infection and high RPS in vaccinated fish. Mohd et al [43] showed high protection in tilapia orally vaccinated using an IWC-vaccines while Huang et al [12] used a live recombinant S. typhimurium vector vaccine encoding the Sip protein and produced high protection levels against S. agalactie . These studies show that both live and inactivated vaccines can produce high protection levels when orally administered in tilapia.…”
Section: Vaccine Delivery Systemmentioning
confidence: 99%
“…Nur-Nazifah et al [13] compared the efficacy of a recombinant vaccine encoding the LPXT cell wall surface anchor family protein of S. agalactiae with an IWC-vaccine in which they showed that both vaccines produced high IgM levels in serum and mucus that corresponded with low post challenge infection and high RPS in vaccinated fish. Mohd et al [43] showed high protection in tilapia orally vaccinated using an IWC-vaccines while Huang et al [12] used a live recombinant S. typhimurium vector vaccine encoding the Sip protein and produced high protection levels against S. agalactie . These studies show that both live and inactivated vaccines can produce high protection levels when orally administered in tilapia.…”
Section: Vaccine Delivery Systemmentioning
confidence: 99%
“…High concentrations of lymphoid cells were observed in the posterior intestine, and support the conclusion that posterior intestine plays a major role in immunity (Buddington and Diamond, 1987). Similarly, Ezeasor and Stokoe (1981) found high phagocytic activities in the posterior intestine compared to another regions while a study in red tilapia revealed accumulation of lymphoid cells in the lamina propria of posterior intestine following oral vaccination with adjuvanted feed-base vaccine against streptococcosis (Firdaus-Nawi et al, 2012). Due to the immunity functions but less nutrient absorptive capacity (Buddington and Diamond, 1987), posterior intestine requires large numbers of lymphoid cells and the lamina propria should be thick to provide enough space for the lymphoid cells.…”
Section: Discussionmentioning
confidence: 92%
“…Besides function as a lubricant for smooth movement of feed particles, mucus also provides innate host defense by acting as a first line of immunity against invasion of harmful pathogen (Kim and Samuel, 2010). Intestinal mucus secreted in fish contains antibody (Grabowski et al, 2004; Firdaus-Nawi et al, 2012), lysozyme (Lie et al, 1989), glycoprotein (Shephard, 1994), complement components, lectins and some antimicrobial agents (Ingram, 1980; Alexander and Ingram, 1992). In this study, goblet cells were found scattered among the epithelial lining in all three regions of the intestine, but showed no significant difference in numbers until 90 days old.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations